Design and Build Project Cost Control Information Systems for Construction Companies - Pandowo, Hedi; Tohari, Hamim; Kusumaningrum, Dian (Journal of Economics and Public Health, 2022)
Cost control is an important instrument to support the success of a business engaged in construction. Work in the field of construction requires a time limit for the completion of work and obeys the provisions of the quality of each item of work and is fully supervised by various parties involved in the implementation of the work. Accuracy in completing the work according to the scheduled schedule and in accordance with the job specifications specified in the work contract is an important element in the assessment of construction work which has an impact on billing project costs. The existence of an information system is a tool for project cost control that is needed to monitor every progress of work that has been done so that data management can be done quickly and accurately. Therefore, this system was built in order to be able to overcome problems such as calculating work unit price analysis, Compiling a Cost Budget Plan, Implementation Budget Plan, Job Costing, Scheduling, Progressing to billing terms that can be done in one integrated information system. Tools used in making this system is Visual Basic. The application design method uses the Togaf method. The results of this study are outlined in the form of a blueprint which is used as a reference in the development of a project cost control information system at PT. Selo Adi Karto. the research results have been analyzed using the chain and TOGAF methods which produce a proposed portfolio of applications that will become data for implementation. The architecture designed which is the result of this research is in the form of an integrated project cost control information system in computer network technology.